VARIASI BAHASA DALAM INTERAKSI SISWA DAN GURU BAHASA INDONESIA DI SMPN 18 PONTIANAK - Purwanti, Purwanti; Muzammil, Ahmad Rabi?ul; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe background of this research problem is the variation of language in the interaction of students and teachers of Indonesia is a sosiolinguistic study. The problem in this research is the form language variation in term of formality and the factors that influence the use of language variation. Methods of observasion (observation) and skills (interview). Qualitative research forms. Data collection techniques, tapping techniques, free conversation skills, note taking techniques, video techniques. The tools is data cards and camera. Based on the results of research on language variation in the interaction of students and lndonesia language teachers in SMPN 18 Pontianak, variations of the language used in interaction are variations of language term of formality, formal variations, consultative variations, casual variations, familiar variations. Casual variations is the most widely used language variations, casual variations is 26 utterances, formal variations 17 utterences, consultative variations 12 utterences, familiar variations 14 utterences . factors influencing the use of language variations in the interaction of students and Indonesia language teachers in class VIIA in junior high school 18 Pontianak. Sosial factors there are 5 data, social status, level of education, age, gender. Situasional factors there are 5 data who speaks in what language, to whom, when, where, abaout what.Keywords: Variation Language, Variation in Term of Formality, Students and Teachers